The Dynamics of Power in the Political Discourse of Najwa Shihab and Prabowo Subianto on the Police Bill (RUU Polri) - Radianti, Ruly Aprilia; Sofyaningrun, Rosita (The Future of Education Journal, 2026)
This study examines the dynamics of power in political discourse through a critical discourse analysis of the dialogue between Najwa Shihab and Prabowo Subianto concerning the Draft Law on the Indonesian National Police. The research aims to reveal how power relations between media and the state are constructed, negotiated, and maintained through language. Employing a qualitative approach, this study applies Norman Fairclough’s three dimensional model of Critical Discourse Analysis, encompassing textual analysis, discursive practice, and social practice. The data consist of fifteen selected excerpts from the televised dialogue, which are analyzed as complete discursive events. The findings indicate that at the textual level, Najwa Shihab employs evaluative diction, oppositional structures, and critical interrogative forms to problematize the draft law and challenge state authority, while Prabowo Subianto utilizes declarative, normative, and imperative expressions to assert legitimacy and institutional power. At the level of discursive practice, the media exercises discursive control by framing issues around public concerns and directing the flow of interaction, whereas the state adopts defensive and justificatory strategies to normalize policy decisions and limit criticism. At the level of social practice, the discourse reflects broader democratic tensions in Indonesia related to transparency, public participation, and the centralization of state power. The study concludes that the dialogue functions not merely as an informative interview but as a political arena where media and state actors compete discursively to shape meaning, legitimacy, and public opinion.